A brief psychological overview of disordered gaming. (December 2020) - Kircaburun, Kagan; Pontes, Halley M; Stavropoulos, Vasileios; Griffiths, Mark D
Highlights: Prevalence of gaming disorder (GD) in representative samples ranges between 1% to 5%. There are many methodological limitations in gaming disorder assessment. GD can co-occur with other psychiatric conditions and other addictive behaviors. Internet gaming disorder and internet addiction are different nosological entities. GD has had treatment success with pharmacotherapy and cognitive-behavioral therapy. Abstract : In the latest (eleventh) revision of the International Classification of Diseases (ICD-11), the World Health Organization (WHO) recognized Gaming Disorder (GD) as an official diagnostic entity. Furthermore, in the latest (fifth) edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), the American Psychiatric Association (APA) proposed Internet Gaming Disorder (IGD) as a tentative disorder in need of further study. The present review provides a brief analysis on the current state of the art of the field. Even though there has been an ongoing debate concerning the proposed diagnostic criteria, there are now a number of assessment tools that have been developed using the diagnostic frameworks devised by the WHO and APA which have provided greater accuracy and consistency in IGD research. The prevalence rates of IGD reported in representative samples have ranged from approximately 1% to 5%. However, the discrepancy in the prevalence rates is mainly due to the reliance on non-representative samples, inconsistent assessment, and conceptual heterogeneity. In terms of treatment approaches, the literature suggests that pharmacological treatment and cognitive behavioral therapy-based treatments have been successfully employed to reduce the symptoms of IGD. Despite the latest clinical advances in IGD research, there are still major drawbacks in treatment and existing intervention studies due to key limitations relating to sample sizes in treatment studies, small effect sizes, and scarcity of research on intervention studies. Taken together, these issues highlight the need for further studies into disordered gaming.